Manejo de solo e água em soja e arroz em terras baixas - Giacomeli, Robson (2019)
The lowland areas with agricultural production in the southern half of Rio Grande do Sul are predominantly cultivated with rice, flood irrigated. This irrigation method uses more water and emits larger amounts of greenhouse gases compared to other methods. In addition, the soils of these areas present low physical quality for aerobic crops, which associated with the low slope, results in problems with water excess and/or deficit for crops. Such characteristics often prevent the rotation of rice with other crops. Given these challenges, experiments were carried out with rice and soybean crops in the 2016/17 and 2017/18 agricultural seasons, which were summarized in two scientific papers. The first paper refers to the experiments with the soybean crop, and aimed to evaluate the effects of irrigation systems and soil management on soil physical properties and soybean growth and grain yield cultivated in lowlands. Two factors were studied, being irrigation systems and soil management. Between the irrigations systems, it was tested sprinkler irrigation, border irrigation and rainfed. For soil management, the treatments were composed by tillage, no-tillage, tillage with raised-seedbed and no-tillage with raised-seedbed. The second scientific paper addresses rice crop and the objective was to evaluate irrigation systems and soil management for rice cultivated in lowlands. It also had two factors, being the irrigation systems composed by the sprinkler, border and flood irrigation and the soil management composed by conventional tillage, no-tillage and conventional tillage with raised-seedbed. In the results, the variables analyzed were the soil physical properties (bulk density, total porosity, soil resistance to penetration, macroporosity and microporosity), irrigation water requirement, root system distribution, yield components, grain yield, total water productivity and irrigated water productivity. Soil management with conventional tillage increases soil resistance to penetration near 0.1 m depth in lowland soils. In years of uneven rainfall, the soil management in no-tillage without irrigation results in an increase of 20% in soybean grain yield compared to conventional tillage non-irrigated, and irrigation increases grain yield by 37%. For rice, sprinkler irrigation resulted in higher irrigation water productivity (3.82 kg m-3), compared to border (1.64 kg m-3) and flood (1.21 kg m- 3). It was concluded that sprinkler irrigation can be used as an alternative to flood irrigation, in no-tillage, for rice and soybean cultivation, with higher irrigation water productivity and that soil management does not interfere with rice grain yield when flood irrigated.